Reflecting on Assessment: Strategies and Tools for Measuring the Impact of a Canadian WAC Program - Kaler, Michael; Evans-Tokaryk, Tyler (Discourse and Writing/Rédactologie, 2019)
This paper provides an overview of the process and tools we have developed for assessing the impact of writing development projects carried out in a wide variety of courses at our university. It begins with an overview of writing studies in Canada to provide context for our approach to writing instruction and writing program assessment. It then offers a case study of a specific writing development project in a large first-year humanities course, a detailed explanation of the methods we used to measure the efficacy of that project, and an exposition of the way in which this assessment was used to drive reflection on the project and enhancement of it. The paper concludes with summary of the lessons we have learned regarding writing program assessment that navigates between creating a standardized process and responding to the unique needs of multiple projects, as well as a discussion of the benefits of such assessment for writing pedagogy research.